The Emerging Engineering Scholar: A Citation Analysis of Theses and Dissertations at Western Michigan University. - Edward J. Eckel (Issues in Science and Technology Librarianship)
Can one glimpse the development of emerging scholars in the work of engineering graduate students? To answer this question, the author studied the citation patterns in 96 Master's theses and 24 Ph.D. dissertations completed at Western Michigan University's College of Engineering and Applied Sciences between 2002 and 2006. The hypothesis of this study is that an increase in graduate student research competence between the master's and doctoral levels can be seen in their use of scholarly sources such as journal articles and conference papers. For each thesis and dissertation, bibliographic information (title, author, document type, year of publication) was gathered for each individual citation in the reference list(s). The data analysis indicates that doctoral engineering students use a significantly greater number of scholarly journal articles (44.3% to 29.3%) and conference papers (21.9% to 12.5%) than master's students. Also, master's students depend more heavily upon literature available on the web (web sites, government papers, grey literature, trade magazines, and patents). These results give tentative support to the hypothesis. Without knowing how faculty expectations influence the quality of graduate literature reviews, the hypothesis could not be conclusively supported with the data gathered. This study shows that there is a significant difference in the proportions of scholarly and other research sources used by master's and doctoral engineering students. The implications of these citation patterns in the development of the engineering scholar are discussed. [ABSTRACT FROM AUTHOR]